Sexism and Attitude Toward Reporting of Child Sexual Abuse - Inke Kusumastuti (Journal of Agromedicine and Medical Sciences, 2021)
Long-standing sexism in the Balinese community, based on its traditional paternalistic culture, may become the main factor to underlie children's vulnerability for abuse. School teachers, considering their regularity to interact with children in schools, might play a significant role in early detection and intervention of such cases. We conducted a cross-sectional observational study by sampling Junior High School teachers in Denpasar as an initial effort to analyze the correlations between sexism and attitude toward reporting of child sexual abuse in Bali. Subjects were requested to complete the questionnaires Ambivalent Sexism Inventory (ASI) and a Teachers’ Reporting Attitude Scale for Child Sexual Abuse (TRAS – CSA). The two scales were then analyzed for correlations. The score of ASI Hostile sexism (HS) domain was inversely correlated with total TRAS-CSA, while a positive correlation was found between total TRAS-CSA score and total ASI Benevolent Sexism (BS) domain score for Paternalism subdomain. This research also pointed to the tendency of the Balinese sample to conduct the practice of benevolent sexism instead of hostile sexism. In correlation with teachers’ reporting for sexual abuse, cautions should be taken for possible inadequate reporting that might potentially lead to the chronicity of the abuse. Keywords: attitude, reporting, child sexual abuse, sexism, teacher